PVP-Stabilized Palladium Nanoparticles in Silica as Effective Catalysts for Hydrogenation Reactions - Caroline Pires Ruas; Daiane Kessler Fischer; Marcos Alexandre Gelesky (Journal of Nanotechnology)
Palladium nanoparticles stabilized by poly (N-vinyl-2-pyrrolidone) (PVP) can be synthesized by corresponding Pd(acac)2 (acac = acetylacetonate) as precursor in methanol at 80°C for 2 h followed by reduction with NaBH4 and immobilized onto SiO2 prepared by sol-gel process under acidic conditions (HF or HCl). The PVP/Pd molar ratio is set to 6. The effect of the sol-gel catalyst on the silica morphology and texture and on Pd(0) content was investigated. The catalysts prepared (ca. 2% Pd(0)/SiO2/HF and ca. 0,3% Pd(0)/SiO2/HCl) were characterized by TEM, FAAS, and SEM-EDS. Palladium nanoparticles supported in silica with a size 6.6 ± 1.4 nm were obtained. The catalytic activity was tested in hydrogenation of alkenes.